Youth Employment Among Female Students at a Private University in Arequipa, Peru: The effects in times of pandemic - Velásquez Chacón, Erika (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of the study is to evaluate university youth unemployment in women between 18 and 30 years of age, as a consequence of the effects of the pandemic on public health. The methodology responds to a field study with a sample of 239 cases analysed through a closed survey, based on 26 items, using a Likert scale to contrast the professional and human situations of the respondents related to conciliation, equality, and professional development. The results showed gaps in women, which require strengthening women’s participation in the workplace.